Sistem Pakar Diagnosa Penyakit Udang Vannamei Menggunakan Metode Forward Chaining Berbasis Web (Studi Kasus : Petambak Udang Dirawajitu) - Davit Wijaya; Machudor Yusman; Akhmad Ikhwan (Universitas Mitra Indonesia, 2022)
One of the causes of failure in pond shrimp farming is disease. The most dangerous disease attacks and causing losses to farmers are due to viral attacks of Myo/Infectious Myo Necrosis Virus (IMNV) of Shrimp, White Spot Syndrome (WSS) of Shrimp, Early Mortality Syndrome (EMS), and Yellow Head Disease. / Yellow Head Disease. The purpose of the research is to build an expert system application that can diagnose pond shrimp disease using the backward chaining method so as to help the community in Rawajitu sub-district in aquaculture shrimp., the system design method used is Unified Modeling Language (UML), the system development method used is Waterfall, and system built using Adobe Dreamweaver 8 tools and MySQL database. The results of this study are the application of an expert system that can diagnose pond shrimp disease using the backward chaining method. The system created later is expected to provide services to shrimp farmers in obtaining information on shrimp disease and accurate disease management solutions.